Lenguaje y hermosura, un tema lingüístico que perdura - MORANT MARCO, Ricard; MARTÍN, Mª Aranzazu (Revista de Filología Románica, 2010)
This paper provides a profound reflection on how the importance our society accords to a good image –which is based on three factors, beauty, youth and thinness– is mirrored in our linguistic expression. Firstly, we explain how our society forces us to pursue rigid aesthetic ideals, which are reflected in language. Then we analyze the cultural perception of the above-mentioned attributes and its reflection in our linguistic environment. Finally, we put forth our conclusions, where we summarize the main ideas dealt with in this paper.